Therapeutic Effect of Combining Anisodamine With Neostigmine on Local Scar Formation Following Roux-en-Y Choledochojejunostomy in a Novel Rat Model - Lyu, Shao-cheng; Wang, Jing; Xu, Wen-li; Wang, Han-xuan; Pan, Fei; Jiang, Tao; He, Qiang; Lang, Ren (Frontiers in Pharmacology, 2021)
Background: The present study aimed to explore the potential effect of combining anisodamine with neostigmine on local scar formation following Roux-en-Y choledochojejunostomy (RCJS) in a novel rat model. Methods: The biliary obstruction model of Sprague Dawley (SD) rats was established in advance, and 54 rats were divided into nine groups randomly (sham operation group, anisodamine group, neostigmine group, combination group, and control group). Anisodamine (25 mg/kg) and neostigmine (50 μg/kg) were injected to the abdominal cavity separately or simultaneously for 1 week since the first day after surgery according to their allocated intervention, while the same amount of saline (0.5 ml) was injected intraperitoneally in the control group. Indexes including body weight, the diameter of the common bile duct, liver function, inflammatory indexes, and the condition of scar formation in different groups at certain time were evaluated in our study. Results: Recovery of liver function (ALT, AST, TB, DB, and GGT) and systematic inflammation indexes (CRP, TNF-α, and IL-1β) in the combination group was prior to that in the control group (p < 0.05), while no statistical difference in the serum level of IL-10 was observed among groups. Rats in the combination group represented a wider anastomotic diameter and lower expression of α-SMA and TGF-β1 at anastomotic stoma compared to the control group (p < 0.05). Histopathological staining showed slighter proliferation of collagen and smooth muscle fibers in rats’ bile duct wall and less local scar formation at anastomotic stoma compared to the control group. Conclusion: The combination of anisodamine and neostigmine can alleviate local and systemic inflammatory response, promote the recovery of liver function, and reduce scar formation in rats after the RCJS procedure.